MicroRNA-181a Inhibits Activated B-Cell-Like Diffuse Large B-Cell Lymphoma Progression by Repressing CARD11. (24th September 2019) - Zhu, Danxia; Fang, Cheng; He, Wenting; Wu, Chen; Li, Xiaodong; Wu, Jun
Abstract : We investigated the role of miR-181a in diffuse large B-cell lymphoma (DLBCL) and its potential target genes. miR-181a levels were lower in activated B-cell- (ABC-) like DLBCL cells than that in germinal center B-cell- (GCB-) like DLBCL cells. Overexpression of miR-181a in ABC-like DLBCL cell lines (OCI-LY10 and U2932) resulted in G0/G1 cell cycle arrest, increased apoptosis, and decreased invasiveness. miRNA target prediction programs (miRanda, TargetScan, and miRDB) identified caspase recruitment domain-containing protein 11 ( CARD11 ) as a putative miR-181a target. CARD11 mRNA and protein levels were higher in the ABC-like DLBCL than that in GCB-like DLBCL. Moreover, CARD11 mRNA and protein levels were downregulated in the OCI-LY10 and U2932 cell lines overexpressing miR-181a. Dual luciferase reporter assays confirmed the miR-181a binding site in the CARD11 3′UTR region. OCI-LY10 and U2932 cells transfected with a CARD11 expression vector encoding miR-181a with a mutated binding site showed higher CARD11 protein levels, cell viability, G2/M phase cells, and invasiveness compared to those transfected with a wild-type CARD11 expression vector. Nude mice xenografted with OCI-LY10 cells with overexpressed wild-type miR-181a generated smaller tumors compared to those with overexpressed mutated binding site of CARD11 3′UTR and miR-181a. These results indicate that miR-181a inhibits ABC-like DLBCL by repressing CARD11 .